Perbedaan Tahapan Pembelajaran Sekolah Lapang Pengelolaan Tanaman Terpadu Padi Sawah antar Komunitas Petani di Lampung - Slameto Slameto; F. Trisakti Haryadi; Subejo Subejo (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2015)
Enhancement of paddies production in Lampung done with implementation of agriculture technology innovation. The effort done with farmer field school of integrated crops management (FFS-ICM) of paddies. The learning of field school occured on various ethnic community of rice farmers. The effectivity of learning process can be occured with impersonation by the stages of attention, retention, behavior production process and motivation. The purpose of this study to analyze the difference effectiveness of learning farmer field school for farmers from ethnic Lampung, Java and Bali. The research methods with survey on rice farmers FFS-ICM of paddies participant. The sample total 286 farmers.The research located in Lampung. The research carried out Juni-September 2013. The data analysis done with the difference variance. The result indicate that only the motivate stages of process learning FFS-ICM between Bali-Java ethnic shows that the obvious difference.That implications need a preparation of learning material which capable to increase farmers motivation, need an improvement empowerment of farmers group, empowering figure roles and farmer society figures.Keywords: stages of learning, farmer field school, paddies, Lampung-Bali-Java ethnic